The Contribution of Myth to Nature Conservation in the Short Story “Queen of Bauxite” by Abdul Kadir Ibrahim: Literary Ecology Review - Tessa Dwi Leoni (Universitas Negeri Semarang, 2022)
Abstrak. The study of the short story “Ratu Bauxit” by Abdul Kadir Ibrahim aims to find out the problems of the natural environment contained in the work, as well as how the relationship between humans and nature as well as the contribution of literature as a human creation to nature conservation. From these short stories, data related to the description of natural problems and their relationship with humans are obtained which are the focus of this study. Data obtained through heuristic reading and recording techniques. Furthermore, the data were analyzed by descriptive qualitative method which refers to ecocritical theory. The results of the analysis show that there is a description of natural damage related to bauxite mining in the Riau Islands region. Environmental damage caused by ongoing bauxite mining also has an impact on the survival of the surrounding community. Thus, there is a need for human awareness to address environmental problems, especially related to the impact of bauxite mining exploitation. Efforts to preserve oral literature in the form of myths related to nature in people's lives can indirectly contributeto the conservation of natural resources.